1‐Butanthiol [MAK value documentation in German language, 2019]. Issue 3 (1st August 2019) - Hartwig, A.; ,
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated the maximum concentration at the workplace (MAK value) of 1‐butanethiol [109‐79‐5 ]. Available publications and unpublished study reports are described in detail. Additional data from a 90‐day inhalation study in rats indicate that the critical effect is haematotoxicity. On the basis of the NOAEC of 9 ml/m 3 and taking into account the increased respiratory volume at the workplace, the MAK value is increased to 1 ml/m 3 . Since a systemic effect is critical, Peak Limitation Category II with an excursion factor of 2 is assigned. The NOAEC for developmental toxicity in mice is 10 ml/m 3 and the NOEC for rats is 152 ml/m 3 . After considering the increased respiratory volume at the workplace, the margin to the MAK value calculated based on the data from the rat is sufficiently large. In mice, the LOAEC for developmental toxicity is 68 ml/m 3 and the NAEC is probably higher than 10 ml/m 3, which results in a sufficient margin to the MAK value. Therefore, damage to the embryo or foetus is unlikely if the MAK value is not exceeded and 1‐butanethiol remains classified in Pregnancy Risk Group C. According to skin absorption models, percutaneous absorption is expected to contribute significantly to systemic toxicity. Therefore, 1‐butanethiol is designated with an "H". 1‐Butanethiol can cause sensitization of the skin in animals and is therefore designated with "Sh".